Desenvolvimento sustentável e energias renováveis : um estudo econômico sobre o potencial de uso do MDL para o desenvolvimento da energia eólica no Espírito Santo - Bolsanello, Renato Ximenes (2010)
The paper analyzes if the Development of Wind Energy in the State of Espírito Santo can be classified as a project that might fit the definitions of Clean Development Mechanism under the Kyoto Protocol, aimed at attracting foreign investment to produce electricity without degrading the environment, as well as generate financial returns to market for Certified Emission Reductions. The growth and development of wind energy presents itself as an important and promising technology to generate additional power clean carbon emissions. In this scenario of global warming, the carbon market can be a way of developing countries through projects of Clean Development Mechanisms (CDM) pursue their sustainable development. This paper presents the evolution of wind energy over time, their use in generating electricity, its Wind Atlas and its perspectives. Considering the wind potential in the state and the new rules of the electricity sector, as well as programs to encourage clean energy sources, a study was developed to prove the possibility of using the Clean Development Mechanism for its deployment in Espírito Santo.